Emerg??ncias de uma metodologia transdisciplinar para educa????o a dist??ncia sob a perspectiva onto-epistemol??gica da complexidade - Santos, Daniel Barbosa (2017)
This doctoral thesis, entitled "Emergencies of a transdisciplinary methodology for distance education under the onto-epistemological perspective of complexity", arises from my concerns about our current educational practice, based on secular models that, even apparently decadent, are still constitute as dominant, establishing an education based on methods and techniques that no longer seduce, not convince and no longer satisfy. When analyzing the practice of Distance Education, while reflecting on the need to redefine the current educational paradigm, I will seek, in Complex Thought and in the transdisciplinary methodology, some macroconcepts that will base this research epistemologically. The investigations regarding the pedagogical actions directed to Distance Education bring to the fore a specific and innovative educational modality that, in a reflexive way, could allow us to reflect on the education itself in its broadest sense. Agglutinating all the reflections proposed in the course of the arguments, the following problem arises to be investigated in this research: from the perspective of the emerging paradigm of complexity, the predominant teaching-learning processes in virtual environments consider the complex ontoepistemological dimensions that lead to a transdisciplinary methodology? From this problematic, the proposed macro-objective for this thesis is to evaluate, in Virtual Learning Environments, the aspects that suggest the overcoming of a cartesian educational paradigm, characterized by actions mainly conservative, linear and reductionist, in favor of a to make an emerging pedagogical one that considers the ontological perspective of the complexity, that favors the adoption of collaborative, innovative methodologies and that contemplates aspects of the transdisciplinarity in the processes of transformation of the apprentice subject.